2004
DOI: 10.1136/gut.2003.031310
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the spinal modulation of nociceptive processing in patients with irritable bowel syndrome

Abstract: Background: Visceral hypersensitivity has been evidenced in patients with irritable bowel syndrome (IBS) but its mechanisms remain poorly elucidated. We investigated the spinal transmission of nociceptive signals in IBS patients by analysing the effects of rectal distensions on electromyographic recordings of the somatic nociceptive flexion (RIII) reflex, an objective index of spinal nociceptive processes. Methods: Fourteen IBS and 10 healthy volunteers were included in the study. Slow ramp (40 ml/min) and rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 30 publications
(31 reference statements)
6
89
2
4
Order By: Relevance
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
“…Twelve studies (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015) (pooled n = 1906) were included in reflex threshold comparisons. Two studies investigated two patient groups (Rhudy et al, 2013;Smith et al, 2013), which increased our group comparisons to 15.…”
Section: Reflex Thresholdmentioning
confidence: 99%
“…A deficit in endogenous pain modulation and somatic hypersensitivity have also been demonstrated in other recent studies in IBS patients (Heymen et al, 2010;Wilder-Smith et al 2004). Moreover, the spinal transmission of nociceptive signals in IBS patients was investigated by analyzing the effects of rectal distensions on EMG recordings of the somatic nociceptive flexion (RIII) reflex, an objective index of spinal somatic nociceptive processes (Coffin et al, 2004). The results indicated that the RIII reflex was significantly facilitated during slow ramp distension, whereas inhibitions induced by rapid distensions were significantly reduced in IBS patients compared to healthy controls (Coffin et al, 2004).…”
Section: Deficit In Pain Inhibition In Ibsmentioning
confidence: 99%
“…In the case of secondary hyperalgesia, descending facilitation predominates over inhibition in pain circuits with input from adjacent tissues (Vanegas & Schaible, 2004). The importance of facilitation of the spinal nociceptive processing has been recently recognized as a potential mechanism contributing to the pathophysiology of chronic pain conditions, including numerous functional disorders, such as IBS (Coffin et al, 2004). In these disorders characterized by persistent pain or discomfort without clearly defined tissue pathology, normally innocuous stimulation is incorrectly interpreted as noxious, which may originate from input to the RVM from sites rostral in the brain (e.g., via cortical, amygdalar or hypothalamic efferents), and be affected by a state of attention, anxiety, or cognitive perception (Urban & Gebhart, 1999).…”
Section: Descending Pain Modulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation